2019
DOI: 10.3390/coatings9090550
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide for Functional Textile Coatings: Recent Advances

Abstract: The use of ZnO for the functionalization of textile substrates is growing rapidly, since it can provide unique multifunctional properties, such as photocatalytic self-cleaning, antimicrobial activity, UV protection, flame retardancy, thermal insulation and moisture management, hydrophobicity, and electrical conductivity. This paper aims to review the recent progress in the fabrication of ZnO-functionalized textiles, with an emphasis on understanding the specificity and mechanisms of ZnO action that impart indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
122
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(127 citation statements)
references
References 149 publications
2
122
0
3
Order By: Relevance
“…Zn was observed to be the most abundant metal in the present study (0.873 mg/L), which is consistent with results reported worldwide [67][68][69][70]. The relatively high concentrations of Zn measured in rainwater of Pachuca (1.174 mg/L) and Tulancingo (1.892 mg/L) were attributed to local sources, i.e., mine tailings and the textile industry, respectively [71,72]. Additionally, Zn can also be sourced from metallic roofs, storage tanks, road transportation, domestic heating, agricultural waste burning, and direct emission from polluted soils.…”
Section: Elemental Ratiossupporting
confidence: 91%
“…Zn was observed to be the most abundant metal in the present study (0.873 mg/L), which is consistent with results reported worldwide [67][68][69][70]. The relatively high concentrations of Zn measured in rainwater of Pachuca (1.174 mg/L) and Tulancingo (1.892 mg/L) were attributed to local sources, i.e., mine tailings and the textile industry, respectively [71,72]. Additionally, Zn can also be sourced from metallic roofs, storage tanks, road transportation, domestic heating, agricultural waste burning, and direct emission from polluted soils.…”
Section: Elemental Ratiossupporting
confidence: 91%
“…Therefore, it is still a challenging task to synthesize highly thermal stable charring-foaming polymers. To increase the strength and the compactness of intumescent chars, some synergistic agents such as zeolite [12,13] and metal-based compounds [14][15][16] were added and investigated successfully. The researchers also reported that synergistic agents accelerated the intumescent mechanism and improved the compactness of chars.…”
Section: Introductionmentioning
confidence: 99%
“…Many functional coatings have been so far proposed and developed. Just recently, for example, gas-barrier thin film coatings for food and beverages [1], the coatings for automotive brake discs [2], tribological coatings [3], functional textile coatings [4], super-hydrophobic anticorrosion coatings [5], and cermet coatings for erosion-corrosion-protection [6] were investigated.…”
Section: Introductionmentioning
confidence: 99%